Why is ethnicity a risk factor for postpartum haemorrhage? - Hashviniya Sekar; Karen Joash (Journal of Obstetrics and Gynaecology)
Postpartum haemorrhage (PPH) is a leading cause of maternal mortality and morbidity on a global scale. Ethnic background is known to be a determinant of variation in the outcomes of women receiving maternity care across the world. Despite free maternity healthcare in the UK National Health Service, women with an ethnic minority background giving birth have an increased risk of PPH, even when other characteristics of the mother, the baby and the care received are considered. Improving PPH care has significant implications for improving health equity. The underlying causes of ethnic disparities are complex and multifaceted. It requires a deep dive into analysing the unique patient factors that make these women more likely to suffer from a PPH as well as reflecting on the efficacy of intra and postpartum care and prophylactic treatment these women receive.